After Paris : Fiscal, Macroeconomic and Financial Implications of Global Climate Change - Farid, Mai (Staff Discussion Notes; Staff Discussion Notes ;, 2016)
This paper discusses the implications of climate change for fiscal, financial, and macroeconomic policies. Most pressing is the use of carbon taxes (or equivalent trading systems) to implement the emissions mitigation pledges submitted by 186 countries for the December 2015 Paris Agreement while providing revenue for lowering other taxes or debt. Carbon pricing in developing countries would effectively mobilize climate finance, and carbon price floor arrangements are a promising way to coordinate policies internationally. Targeted fiscal measures that are tailored to national circumstances and robust across climate scenarios are needed to counter private sector under-investment in climate adaptation. And increased disclosure of carbon footprints, stress testing of asset values, and greater proliferation of hedging instruments, will facilitate low-emission investments and climate risk diversification through financial markets.